Introducing unadapted, insect-resistant maize germplasm in three-way hybrid combinations for resistance to the maize stalk borer, Buáeola fusca (Fuller) (Lepidoptera : Noctuidae) - Van Rensburg, J.B.J.
Sumario (En)